CHIMPS2: survey description and 12CO emission in the Galactic Centre. Issue 4 (10th September 2020) - Eden, D J; Moore, T J T; Currie, M J; Rigby, A J; Rosolowsky, E; Su, Y; Kim, Kee-Tae; Parsons, H; Morata, O; Chen, H-R; Minamidani, T; Park, Geumsook; et al.
ABSTRACT: The latest generation of Galactic Plane surveys is enhancing our ability to study the effects of galactic environment upon the process of star formation. We present the first data from CO Heterodyne Inner Milky Way Plane Survey 2 (CHIMPS2). CHIMPS2 is a survey that will observe the Inner Galaxy, the Central Molecular Zone (CMZ), and a section of the Outer Galaxy in 12 CO, 13 CO, and C 18 O (J = 3→ 2) emission with the Heterodyne Array Receiver Program on the James Clerk Maxwell Telescope (JCMT). The first CHIMPS2 data presented here are a first look towards the CMZ in 12 CO J = 3 → 2 and cover -3^° 5^° and b 0_.^° 5 with angular resolution of 15 arcsec, velocity resolution of 1 km s −1, and rms Δ T_A ^* = 0.58 K at these resolutions. Such high-resolution observations of the CMZ will be a valuable data set for future studies, whilst complementing the existing Galactic Plane surveys, such as SEDIGISM, the Herschel infrared Galactic Plane Survey, and ATLASGAL. In this paper, we discuss the survey plan, the current observations and data, as well as presenting position–position maps of the region. The position–velocity maps detect foreground spiral arms in both absorption and emission.